2022
DOI: 10.1177/14799731221114266
|View full text |Cite
|
Sign up to set email alerts
|

The Recovery Journey and the Rehabilitation Boat - A qualitative study to explore experiences of COVID-19 rehabilitation

Abstract: Introduction There are early data to suggest that a rehabilitation programme can help with on-going symptoms of COVID-19, including breathlessness, exercise limitation and fatigue. As yet, there are no published data to understand patients’ perceived acceptability of a rehabilitation programme for COVID-19. Methods 2 focus groups ( n = 9) and 4 one to one interviews were conducted with participants who attended a rehabilitation program following COVID-19. Interviews were analysed using reflexive thematic analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
4
4
0
Order By: Relevance
“…Research has shown that social isolation and inactivity can result into despair (48,49). On the other hand, studies have reported that positive attitude toward life can help adopt a healthier lifestyle, which is a lesson learned from the pandemic (50)(51)(52). Consistent with previous work, our study also observed change in lifestyle as one of the direct outcomes of the pandemic.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Research has shown that social isolation and inactivity can result into despair (48,49). On the other hand, studies have reported that positive attitude toward life can help adopt a healthier lifestyle, which is a lesson learned from the pandemic (50)(51)(52). Consistent with previous work, our study also observed change in lifestyle as one of the direct outcomes of the pandemic.…”
Section: Discussionsupporting
confidence: 91%
“…A study in China reported similar experience that COVID-19 brought survivors closer to their family and friends (52). However, in explaining rehabilitation needs of COVID-19 survivors a study indicated that patients sometimes tended to refrain from sharing their experience of physical and psychological symptoms to spare their family members (50,56). Thus, culturally appropriate interventions to address future pandemics are desirable where the State can include family members in the rehabilitation process of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Various publications confirm the perceptions of some participants in this study and suggest that rehabilitation programs tailored to individual needs and abilities lead to improvements in physical symptoms, performance, well-being, and quality of life for patients with long COVID [ 14 , 77 – 80 ]. Several studies report that multidisciplinary rehabilitation consisting of physical activity, disease-specific knowledge building, and psychotherapy sessions is helpful for affected individuals [ 80 82 ].…”
Section: Discussionsupporting
confidence: 78%
“…Currently, no treatments targeting the cause of the condition have been approved [ 7 ]. Research suggests that adapted rehabilitation interventions have a positive impact on the recovery process of people with long COVID [ 14 – 16 ]. Furthermore, studies show that first rehabilitation programs developed for long COVID patients [ 16 ] and certain existing programs adapted to the needs of those affected (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, individual participants noted modest relief of symptoms following certain pharmaceutical and non-pharmaceutical treatments (e.g., dietary changes, physical therapy) [43]. Similar to the respondents from this sample, other studies also indicate that group meetings supported by psychotherapists, tailored training programs with strength and endurance exercises, and adapted rehabilitation measures have a positive in uence on the recovery process of affected individuals [6], [49]- [51]. Davies et al [52] emphasize that close follow-up with people with long COVID during the rehabilitation process and education about health conditions are essential.…”
Section: Key Ndings Experience Of Therapiessupporting
confidence: 56%